THE MODEL OF BIOPIRACY DISPUTE SETTLEMENT IN THE FRAMEWORK OF PROTECTING TRADITIONAL KNOWLEDGE - Zakki Adlhiyati; H Harjono; Sri Wahyuningsih Yulianti; Moch Najib Imanullah (Jurnal Dinamika Hukum, 2016)
Solving the problem of traditional knowledge biopiracy faced by Indonesia is the background of this article. Thereby the problem of this papers is to seek the best way to settle the dispute occurred in biopiracy case. Due to the economic value of traditional knowledge this national resources need to be protected. Due to this economic value, a lot of traditional knowledge stolen and patented by someone else, this biopiracy cases had been long faces by the developing countries i.e Indonesia with shisheido case and avian influenza (H5NI) case, India with turmeric case and basmati rice case. Judicial settlement of dispute, alternative dispute resolution, quasi-judicial is a way to solve the cases which can be chosen.Keywords: biopiracy, traditional knowledge, dispute